Self-organization of TiO2 Nanobamboos by Anodization with Deep Eutectic Solvent. (20th January 2015) - Chen, Chun-Yi; Ozasa, Kazunari; Kitamura, Fusao; Katsumata, Ken-ichi; Maeda, Mizuo; Okada, Kiyoshi; Matsushita, Nobuhiro
Abstract: We report an unconventional electrochemical spontaneous oscillation of current in Ti anodization by adding deep eutectic solvent (DES) of 2–10% to a fluoride-containing electrolyte; nanobamboos (NBs), i.e., nanotubes decorated with periodic exterior rings, were formed by the DES-assisted anodization. Spontaneous formation of NBs occurred upon application of a constant 20 V voltage, together with a self-induced current oscillation that corresponds well to the NB structures. The initial voltage must be higher than a threshold of approximately 14 V to induce the self-organization of the NBs. Once a dense layer of TiO2 is formed at 10 V or lower, formation of the NBs is suppressed even when a higher voltage (above 15 V) is applied. The NBs formed with the spontaneous current oscillation were densely packed (ca. 1.54 × 10 10 cm −2 ) with each NB possessing many rings spaced 20–35 nm apart. The thickness of each ring was ca. 10 nm. By increasing the DES concentration to 10 wt%, the diameter of the NBs increased from 45 to 110 nm and their growth rate increased from 0.16 to 0.3 μm/h. The spontaneous current oscillation we observed differs from the conventional electrochemical oscillation because (1) oscillation period is quite long (7 min) and (2) the oscillation results in the periodic modulation of TiO2 NBs. The self-organized nanobaoboos were characterized for various anodization conditions, and a mechanism was proposed with the basis of the high conductivity and high viscosity of DES.